China’s Participation in Global Climate Governance: From Paris Agreement to Carbon Neutrality - Wang, Rui; Zhang, Yuting (Law and Economy, 2025)
This paper examines China’s evolving role in global climate governance from the Paris Agreement to its 2060 carbon neutrality commitment. It argues that China’s transformation from a defensive participant to a proactive leader reflects a deep structural integration of environmental law, economic reform, and international diplomacy. The analysis outlines six dimensions of this evolution: the historical trajectory of China’s climate diplomacy, the development of domestic legal and policy frameworks, the economic restructuring toward carbon neutrality, multilateral and bilateral cooperation strategies, the tensions between development and decarbonization, and prospective pathways for sustainable governance. Drawing on data from the International Energy Agency and China’s National Bureau of Statistics, the paper highlights measurable progress, including a 48% decline in carbon intensity since 2005 and global leadership in renewable energy capacity. However, challenges such as regional disparities, coal dependency, and legal enforcement gaps continue to constrain China’s transition. The study concludes that China’s future success will depend on institutionalizing climate law, accelerating technological innovation, and strengthening equitable international cooperation. By aligning national development with global sustainability, China is positioned to play a defining role in shaping the next phase of global climate governance.